2019
DOI: 10.1111/aogs.13558
|View full text |Cite
|
Sign up to set email alerts
|

Balloon catheter for induction of labor in women with one previous cesarean and an unfavorable cervix

Abstract: Introduction When women with a previous cesarean section and an unfavorable cervix have an indication for delivery, the choice is to induce labor or to perform a cesarean section. This study aims to assess the effectiveness and safety of a balloon catheter as a method of induction of labor in women with one previous cesarean section and an unfavorable cervix compared with an elective repeat cesarean section. Material and methods We performed a prospective cohort study in 51 hospitals in the Netherlands on term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 21 publications
4
33
0
13
Order By: Relevance
“…In our study, 7.5% of women with prior CS were induced with prostaglandins during the time period 2013-2018 and the rate did not decline after 2016 (result not presented). In concordance to prior reports, 9,23 we also found that women induced with a cervical catheter had no increased risk of uterine rupture. A systematic review of eight randomized controlled trials encompassing 707 women induced after a prior CS concluded that the studies were underpowered to detect clinically important outcomes such as uterine rupture and there was no clear evidence on the most efficient or safe method of induction in women with a prior CS.…”
Section: Accepted Articlesupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, 7.5% of women with prior CS were induced with prostaglandins during the time period 2013-2018 and the rate did not decline after 2016 (result not presented). In concordance to prior reports, 9,23 we also found that women induced with a cervical catheter had no increased risk of uterine rupture. A systematic review of eight randomized controlled trials encompassing 707 women induced after a prior CS concluded that the studies were underpowered to detect clinically important outcomes such as uterine rupture and there was no clear evidence on the most efficient or safe method of induction in women with a prior CS.…”
Section: Accepted Articlesupporting
confidence: 92%
“…[2][3][4] The rate of uterine rupture in women attempting a trial of labor after one previous low transverse CS has been estimated at between 0.2% and 1.5%, reflecting that selection for and management of trial of labor differ between healthcare settings and countries. 1,2,5,6,7,8,9 Efforts to improve safety of vaginal delivery after CS have focused on the identification of risk factors for uterine rupture, but few studies have examined the actual course of labor. [10][11][12] Recognition of clinical signs of uterine rupture is challenging due to the lack of specific symptoms; moreover, most signs do not precede, but follow, uterine rupture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aOR 1,32; 95 %-KI 0,37-4,72). Uterusrupturen nach Ballonkathetereinlage treten in der Regel nicht während der Zervixreifungsphase, sondern während der intravenösen Gabe von Oxytocin auf [21,36]. Nach intravenöser Anwendung von Oxytocin zur Geburtseinleitung nach Sectio wurde über eine Frequenz von Uterusrupturen von im Mittel 1,4 % (0,4-2,3 %) berichtet [5,41], die um das bis zu 3-Fache höher liegt als nach Abwarten spontaner Wehen [5,43].…”
Section: Diskussionunclassified
“…Auch die Frage, ob bei medizinischer Indikation die Geburtseinleitung einer elektiven Re-Sectio vorzuziehen ist, bleibt unter Be-rücksichtigung von nur einer aktuellen Studie mit fehlender Randomisierung [36] unbeantwortet.…”
Section: Schlussfolgerungenunclassified